Comparative characteristics of anthropometric data and indicators cardiovascular cyclists category MASTERS different age groups - Victoria Gorinа; Sergey Kotlyar; Tatiana Sidorova (Kharkiv State Academy of Physical Culture, 2015)
Purpose: the study of the functional state of athletes cyclists category MASTERS different age groups. Material and Methods: the study was conducted using anthropometric testing and measurement of the cardiovascular system. The study involved three groups of cyclists category MASTERS different age groups: I group 40-44 years; II group 45-49 years; group III 50-54 and older. Results: the analysis of the research data and anthropometric indicators of cardiovascular category MASTERS athletes of different age groups in relation to indicators in active sports shows that significant changes have occurred in larger number of indicators, in addition to growth athletes. Conclusions: test measurements allow enough informative to compare the features of athletes of different age groups and found opportunities for correction and control training process cyclists category MASTERS.